2012
DOI: 10.1103/physrevb.86.121108
|View full text |Cite
|
Sign up to set email alerts
|

Graphene hyperlens for terahertz radiation

Abstract: We propose a graphene hyperlens for the terahertz (THz) range. We employ and numerically examine a structured graphene-dielectric multilayered stack that is an analogue of a metallic wire medium. As an example of the graphene hyperlens in action we demonstrate an imaging of two point sources separated with distance $\lambda_{0}/5$. An advantage of such a hyperlens as compared to a metallic one is the tunability of its properties by changing the chemical potential of graphene. We also propose a method to retrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 25 publications
1
64
0
Order By: Relevance
“…It was theoretically shown that graphene supports surface plasmon polaritons in the terahertz and infrared ranges [7][8][9][10][11][12][13][14][15] and can be a building material for metamaterials, which provide a wider range of electromagnetic properties than continuous graphene. Therefore continuous and structured graphene allows for an ultimate terahertz radiation control resulting in functional devices [16], such as modulators [17][18][19], hyperlenses [20], tunable reflectors, filters, absorbers and polarizers [21][22][23][24]. In this paper we will focus on graphene absorber.…”
Section: Introductionmentioning
confidence: 99%
“…It was theoretically shown that graphene supports surface plasmon polaritons in the terahertz and infrared ranges [7][8][9][10][11][12][13][14][15] and can be a building material for metamaterials, which provide a wider range of electromagnetic properties than continuous graphene. Therefore continuous and structured graphene allows for an ultimate terahertz radiation control resulting in functional devices [16], such as modulators [17][18][19], hyperlenses [20], tunable reflectors, filters, absorbers and polarizers [21][22][23][24]. In this paper we will focus on graphene absorber.…”
Section: Introductionmentioning
confidence: 99%
“…We also show a detailed study about the dependence of power spectrum emitted by a dipole source in the proximity of the graphene-based HM on the number of layers, as well as on frequency. Alternative to the HM implemented as a graphene-dielectric multilayer studied here, in [25] graphene stripes analogous to a metallic wire medium, are utilized for realizing hyperbolic dispersion in cylindrical wavenumber coordinates, with the aim of designing a hyperlens. The peculiar electronic properties of graphene [26,27], have been investigated for different electromagnetic applications such as lensing [28], transformation optics [29], nanomechanical resonators [30], and solar cells [31].…”
Section: Introductionmentioning
confidence: 99%
“…19) Alternately aligned graphene and metal gratings were designed to achieve Fano-type resonance by exploiting their different responses to electromagnetic waves. 22) Furthermore, metamaterials based on graphene/dielectric multilayers have also been studied both theoretically 23,24) and experimentally. 25,26) The strong coupling between the surface plasmon polaritons in graphene sheets makes graphene a powerful material for controlling wave radiation 27) and for designing ultrasensitive modulators.…”
mentioning
confidence: 99%